2021
DOI: 10.3390/life11010023
|View full text |Cite
|
Sign up to set email alerts
|

Chilblain-Like Lesions during COVID-19 Pandemic: The State of the Art

Abstract: SARS-CoV-2 infection has spread all over the world in the last year, causing millions of COVID-19 cases among humans with a large variability of symptoms and signs, including those on the skin. Among these, a contemporary cluster of chilblain-like lesions with no certain relationship with the infection has been reported. The aim of this paper is to delineate a profile of chilblain-like lesions and to establish the state-of-the-art knowledge about this new phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…However, a high number of cutaneous manifestations have also been reported. Acral lesions resembling those of chilblains are the most reported signs in young adults with a pauci or asymptomatic viral course, 3 whereas maculo-papular and vesicular rashes are the most common in middle-aged patients. [4][5][6] It is still debated whether the skin manifestations are a direct consequence of COVID-19 pathogenicity or a consequence of thrombogenic and immune deregulatory responses triggered by SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high number of cutaneous manifestations have also been reported. Acral lesions resembling those of chilblains are the most reported signs in young adults with a pauci or asymptomatic viral course, 3 whereas maculo-papular and vesicular rashes are the most common in middle-aged patients. [4][5][6] It is still debated whether the skin manifestations are a direct consequence of COVID-19 pathogenicity or a consequence of thrombogenic and immune deregulatory responses triggered by SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…CLL are similar in morphology to chilblains, located mostly on the feet, with acrocyanosis and erythematous–oedematous lesions, or in some cases, bullous and necrotic lesions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…After an initial phase of confusion and disagree among researchers, CLL are nowadays considered a highly likely immune-mediated reaction to SARS-CoV-2 usually observed in healthy asymptomatic young people, whose COVID status is often unremarkable. [1][2][3][4][5][6] It has been postulated that this apparent contradiction could be explained as virus-induced interferonopathy associated with a strong activation of innate immune system and fast clearance of antibodies. 7,8 Recently, Davido et al 9 reported a similar case in a 41-yearold woman developing 'blue toes' after BNT162b2 mRNA COVID-19 vaccine.…”
mentioning
confidence: 99%